Penyisipan Media Teks dan Citra Menggunakan Teknik Steganografi pada Media Pembawa Citra Digital - Alim Muadzani; Oky Dwi Nurhayati; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2016)
Information has now become an  important comodity in human life, with the rapid development of communications technology has enable people to communicate and exchange information more easily. Internet is very popular and used by billions users worldwide, the information passing through the internet is very large, and some certain people trying to get this information for profit. The information need to be secured to prevent the others to get the information that send through the internet, steganography can be used to  hide the information before sending it and the receiver can recover the hidden data. Digital steganography using computer can use a variety of digital file, digital image file is one of them. With the infomation being hidden inside the image-carrier, the others will not aware about the hidden information. Application created using C# programming leanguage and the steganoraphy method using Least Significant Bit Insertion (LSBI). Microsoft Visual Studio used as Integrated Development Environtment (IDE) to code and design the user interface. Software develpment model using Extreme Programming, and the testing using black box method. Application designed to hide text or image inside an image-carrier and the hidden text or image can be recovered. The result of this research are an application that can hide text or image into  image-carrier, and the hidden text or image can be recovered. Based on the testing application can run as expected and fulfill all the requirements.